CLINICAL TRIALS IN DERMATOLOGY – PART II - César, Artur; Mota, Alberto; Azevedo, Filomena (Journal of the Portuguese Society of Dermatology and Venereology, 2015)
The increasing number of clinical trials in dermatology requires from the dermatologist the ability to evaluate the quality, understand, and synthesize information from multiple sources in order to make decisions regarding the therapeutic/ diagnostic strategies. This medical education article explains basic principles, relevant and adapted to the dermatology area, fundamental to an appropriate interpretation of outcomes of clinical trials. Part II of this article discusses the different analysis methods in clinical trials.